Two Versions of the Same Narrative – Astrid Lindgren’s Mio, min Mio in Swedish and Danish - Steffensen, Anette (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2003)
AbstractThis article is in part a review of the literary qualities of the narrative tales written by the Swedish children’s author Astrid Lindgren and in part a comparative reading of the Swedish Mio, min Mio (Mio, my son) and its Danish translation from 1955. It will be shown how the Danish version has been adapted from the Swedish and how as a result the Danish version of the narrative does not have the same literary quality as the original.